EcoAir portable purifier - Ismail, An Nur Nabila; Norzulaidy, Nur Maisyarah Aqisya; Abdul Muhaimin, Izzah Insyirah; Kamaruzaman, Nur Syazwani; Azlan, Adrianna Mia Sara (Academica Press Solutions, 2025)
Air pollution significantly affects health, with urban populations facing constant exposure to pollutants indoors and outdoors. Current portable air purifiers either lack affordability, portability, or child-friendliness, limiting their usage in everyday life. The EcoAir Portable Purifier aims to address these challenges by designing a compact, user-friendly, and affordable device that seamlessly integrates into daily routines. This device will target key demographics like office workers, students, commuters, and parents, providing a sustainable and effective solution for cleaner air